E3 Ligase FBXW7 Facilitates Mycobacterium Immune Evasion by Modulating TNF-α Expression - Song, Jingrui; Chao, Jin; Hu, Xiaohong; Wen, Xin; Ding, Cairong; Li, Dan; Zhang, Ding; Han, Shanshan; Yu, Xiang; Yan, Bo; Jin, Zhu; Song, Yinhong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Tumor necrosis factor alpha (TNF-α) is a crucial factor in the control of Mycobacterium tuberculosis (Mtb) infection. Pathogenic mycobacteria can inhibit and/or regulate host cell TNF-α production in a variety of ways to evade antituberculosis (anti-TB) immunity as well as facilitate immune escape. However, the mechanisms by which TNF-α expression in host cells is modulated to the benefit of mycobacteria is still an interesting topic and needs further study. Here, we report that macrophages infected with Mycobacterium marinum (Mm)—a close relative of Mtb—upregulated the expression of E3 ubiquitin ligase FBXW7. Specific silencing FBXW7 with small interfering RNA (siRNA) significantly elevates TNF-α expression and eventually promotes the elimination of intracellular bacteria. In turn, overexpression of FBXW7 in Raw264.7 macrophages markedly decreased TNF-α production. Furthermore, partial inhibition of FBXW7 in an Mm-infected murine model significantly reduced TNF-α tissue content, alleviated tissue damage as well as reduced the bacterial load of mouse tails. Finally, FBXW7 could decrease TNF-α in a K63-linked ubiquitin signaling dependent manner. Taken together, our study uncovered a previously unknown role of FBXW7 in regulating TNF-α dynamics during mycobacterial infection, which provides new insights into understanding the role of FBXW7 in anti-tuberculosis immunity and its related clinical significance.